An integrated biomanufacturing platform for the large-scale expansion and neuronal differentiation of human pluripotent stem cell-derived neural progenitor cells. (1st July 2018) - Srinivasan, Gayathri; Morgan, Daylin; Varun, Divya; Brookhouser, Nicholas; Brafman, David A.
Graphical abstract: Abstract: Human pluripotent stem cell derived neural progenitor cells (hNPCs) have the unique properties of long-term in vitro expansion as well as differentiation into the various neurons and supporting cell types of the central nervous system (CNS). Because of these characteristics, hNPCs have tremendous potential in the modeling and treatment of various CNS diseases and disorders. However, expansion and neuronal differentiation of hNPCs in quantities necessary for these applications is not possible with current two dimensional (2-D) approaches. Here, we used a fully defined peptide substrate as the basis for a microcarrier (MC)-based suspension culture system. Several independently derived hNPC lines were cultured on MCs for multiple passages as well as efficiently differentiated to neurons. Finally, this MC-based system was used in conjunction with a low shear rotating wall vessel (RWV) bioreactor for the integrated, large-scale expansion and neuronal differentiation of hNPCs. Overall, this fully defined and scalable biomanufacturing system will facilitate the generation of hNPCs and their neuronal derivatives in quantities necessary for basic and translational applications. Statement of Significance: In this work, we developed a microcarrier (MC)-based culture system that allows for the expansion and neuronal differentiation of human pluripotent stem cell-derived neural progenitor cells (hNPCs) under defined conditions. In turn, this MC approach was implemented in a rotating wall vessel (RWV) bioreactor for the large-scale expansion and neuronal differentiation of hNPCs. This work is of significance as it overcomes current limitations of conventional two dimensional (2-D) culture systems to enable the generation of hNPCs and their neuronal derivatives in quantities required for downstream applications in disease modeling, drug screening, and regenerative medicine.